Review Literature: Pelatihan Dan Kompensasi Terhadap Kinerja Karyawan - Tholib, Syavalma Zahwa Az- zahra; Sersanti, Febiola Dwi; Radita, Vellycia Dwi Cintia; Rahmawati, Chinta Isya (PRAGMATIS, 2025)
Training is a systematic process to improve employee knowledge, skills, and attitudes so that they can work more effectively and efficiently, and support the achievement of organizational goals. Meanwhile, compensation is a form of imbalance given by a company or organization to employees as a reward for contributions or work that has been done. Training and funding in various studies are often used to measure employee performance. This research method uses an approach based on a Systematic Literature Review (SLR) 21 articles taken from several national and international journals. The results of the study found that training and compensation provided, both financial and non-financial, which are carried out consistently will have good employee productivity, work efficiency. The training and incentive variables depend on the sector, training method and types of incentives and the context in the organization. Several studies also emphasize that the importance of strategic planning in training design and fair system improvements are useful for encouraging and improving employee performance continuously or sustainably. Furthermore, this study also shows that training that is carried out continuously can increase employee adaptation capacity to the dynamics of the work environment. In addition, fulfillment that is applied fairly and in accordance with employee needs and contributions is an important factor in maintaining loyalty and work motivation. Mediating variables such as job satisfaction, motivation, and organizational commitment also play an important role in strengthening the relationship between training and compensation on performance. This study recommends that organizations need to develop a good training and recovery system that is oriented towards measurable work results, taking into account the characteristics of each sector and organizational culture.